PENGARUH KOMPENSASI, BEBAN KERJA DAN KOMUNIKASI ORGANISASI TERHADAP KINERJA KARYAWAN DI PT PLN BALI UTARA - Three Indah Pratiwi, Komang Ayu; Kartikadewi, Riana (Komunitas Manajemen Kompetitif, 2024)
Increasing employee performance will bring progress for the company to be able to survive in an unstable competitive business environment. Therefore, efforts to improve employee performance are the most serious management challenges because success in achieving company goals and survival depends on the quality of performance of the human resources within it. This research aims to determine the influence of compensation, workload and organizational communication on employee performance at PT. PLN North Bali.This research was conducted at PT. PLN (Persero) North Bali Area, Jl. Udayana No. 27 Singaraja, Buleleng, Bali, Indonesia because problems were found related to the decline in employee performance, apart from that there were problems with organizational justice and low employee job satisfaction. The population in this study were 98 employees of PT PLN North Bali. The sample in this study was taken from the target population, namely 98 people.Based on the research results, it is known that compensation has a significant effect on employee performance, workload has a significant effect on employee performance and organizational communication has a significant effect on employee performance.